2020
DOI: 10.1002/ptr.6895
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting pharmacological potentials of Nigella sativa seed: A promising option for COVID‐19 prevention and cure

Abstract: Nigella sativa seed and its active compounds have been historically recognized as an effective herbal panacea that can establish a balanced inflammatory response by suppressing chronic inflammation and promoting healthy immune response. The essential oil and other preparations of N. sativa seed have substantial therapeutic outcomes against immune disturbance, autophagy dysfunction, oxidative stress, ischemia, inflammation, in several COVID‐19 comorbidities such as diabetes, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 162 publications
(243 reference statements)
0
45
0
1
Order By: Relevance
“…Preclinical studies have shown that constituents in the methanolic extract of N. sativa seeds are responsible for the bronchodilator effect [93]. Recently, N. sativa has been regarded as a potential therapy for COVID-19 [13,18,94,95]. For example, in a molecular docking-based study N. sativa inhibited SARS-CoV2 [94].…”
Section: Nigella Sativa (Black Seed) -Anti-inflammatory and Respiratory Support 61 Nigella Sativa In Covid-19mentioning
confidence: 99%
“…Preclinical studies have shown that constituents in the methanolic extract of N. sativa seeds are responsible for the bronchodilator effect [93]. Recently, N. sativa has been regarded as a potential therapy for COVID-19 [13,18,94,95]. For example, in a molecular docking-based study N. sativa inhibited SARS-CoV2 [94].…”
Section: Nigella Sativa (Black Seed) -Anti-inflammatory and Respiratory Support 61 Nigella Sativa In Covid-19mentioning
confidence: 99%
“…TQ may thus also be helpful in patients infected with COVID-19 where it can relieve some comorbidity. 13 Serious COVID-19 complications include ARDS, pneumonia and multi-organ failure, and the risk of all of these is increased in patients with diabetes and cardiovascular diseases. 141 , 142 N. Sativa has been shown to reduce plasma glucose levels and control haemoglobin-A1c, 143 while intraperitoneal administration of TQ has been demonstrated to substantially decrease hyperglycemia in streptozotocin-induced diabetes in the rats.…”
Section: The Effect Of Thymoquinone On Comorbiditiesmentioning
confidence: 99%
“… 12 Pharmacological intervention using natural products is considered another example of alternative medicine. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of such review articles analysed the phytochemicals from Indian medicinal plants, such as Withania somnifera and Azadirachta indica , as potential inhibitors of SARS‐CoV‐2 targets (Parida et al, 2020). Remedies reviewed more in depth include Nigella sativa (Islam, Hossain, et al, 2020), a plant mainly used for the control of lipid levels and hyperglycaemia (Hallajzadeh et al, 2020), the flavonoids quercetin (Derosa, Maffioli, D'Angelo, & Di Pierro, 2020) and naringenin (Tutunchi, Naeini, Ostadrahimi, & Hosseinzadeh‐Attar, 2020), bee product compounds (Lima, Brito, & da Cruz Nizer, 2020), glycyrrhizin from Glycyrrhiza glabra (Chrzanowski, Chrzanowska, & Grabon, 2020) and curcumin (Zahedipour et al, 2020), a widely used and clinically evaluated nutraceutical (Pagano, Romano, Izzo, & Borrelli, 2018).…”
mentioning
confidence: 99%